Expressive Speech Acts and Cultural Values in Collection of Short Stories Wahah al-Asdiqa’ - Anggraeni, Syifa Fauziah; Tajuddin, Shafruddin; Nuruddin, Nuruddin (UIN Maulana Malik Ibrahim Malang, 2018)
This study aims to describe expressive speech acts and cultural values of Arab society contained in a collection of short stories Wahah al-Asdiqa’. This research uses qualitative approach with content analysis method. First, the researcher reads and studies the data, then records some expressive speech acts, after that she classifies and analyzes the speech into expressive speech acts and cultural values of Arab society, and most recently interpretes the data. The data analysis found that in the Wahah al-Asdiqa’ there are eight types of thanks using expressive speech acts, one replies from thank you, five apologies, seven greetings, two congratulations, fourty praises, five sad expressions, fourteen joyful expressions, and three offensive words, and there are some values of Arabic culture such as language, art, religion, technology, occupation, social organization, and science. Most of the culture of Arab society is based on the teachings of Islam, such as how to greet, praise always given to God, stories of prophets, culture makes poetry, etc. The expressive speech acts and cultural values must be taught to the Arabic students to improve expressive speech acts and have multicultural competence in communicating. Kajian ini bertujuan untuk mendeskripsikan tindak tutur ekspresif dan nilai-nilai budaya dalam masyarakat Arab dalam kumpulan cerita pendek Wahah al-Asdiqa’. Penelitian ini menggunakan pendekatan kualitatif dengan metode konten analisis. Pertama, peneliti membaca dan mengkaji data lalu mencatat tindak tutur ekspresif, setelah itu mengklasifikasi dan menganalisis perkataan tersebut dalam tindak tutur ekspresif dan nilai-nilai budaya dalam masyarakat Arab, dan kemudian menginterpretasikan data. Berdasar hasil analisis, ada delapan tipe ucapan berterima kasih yang menggunakan tindak tutur ekspresif, satu respon dari ucapan terima kasih, lima permintaan maaf, tujuh sapaan, dua ucapan selamat, 40 pujian, lima ungkapan sedih, 14 ungkapan bahagia, dan tiga kata hinaan, selain itu ada beberapa nilai budaya Arab seperti bahasa, seni, agama, teknologi, mata pencaharian, organisasi sosial, dan ilmu. Kebanyakan budaya masyarakat Arab didasarkan pada pengajaran Islam, seperti cara menyapa, pujian terhadap Tuhan, kisah-kisah nabi, budaya membuat puisi, dan sebagainya. Tindak tutur ekspresif dan nilai budaya harus diajarkan kepada siswa yang mempelajari Bahasa Arab untuk meningkatkan tindak tutur ekspresif dan memiliki kompetensi multi kultural dalam berkomunikasi.